2005
DOI: 10.1016/j.pediatrneurol.2004.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypothermia in neonatal encephalopathy: Safety outcomes

Abstract: Hypoxic-ischemic injury may cause multisystem organ damage with significant aberrations in clotting, renal, and cardiac functions. Systemic hypothermia may aggravate these medical conditions, such as bradycardia and increased clotting times, and very little safety data in neonatal hypoxic-ischemic injury is available. This study reports a multicenter, randomized, controlled pilot trial of moderate systemic hypothermia (33 degrees C) vs normothermia (37 degrees C) for 48 hours in infants with neonatal encephalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(150 citation statements)
references
References 11 publications
5
141
2
2
Order By: Relevance
“…Our observational study, although non-randomized and from a single center, represents the largest number of asphyxiated newborns studied to examine the differential effect of WBC versus SHC on multiorgan system dysfunction. 6,7 Similar to other large cooling trials, 6,7,14 the laboratory parameters chosen to assess multiorgan dysfunction reported in our infants actually reflect the net effect of expected postnatal fluctuations and ongoing corrections aimed at normalizing these parameters, in addition to the effects of cooling itself on these organs. Abbreviations: CI, confidence interval; ECMO, extracorporeal membrane oxygenation; FFP, fresh frozen plasma; OR, odds ratio; PPHN, persistent pulmonary hypertension of the newborn; SHC, selective head cooling; WBC, whole body cooling.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our observational study, although non-randomized and from a single center, represents the largest number of asphyxiated newborns studied to examine the differential effect of WBC versus SHC on multiorgan system dysfunction. 6,7 Similar to other large cooling trials, 6,7,14 the laboratory parameters chosen to assess multiorgan dysfunction reported in our infants actually reflect the net effect of expected postnatal fluctuations and ongoing corrections aimed at normalizing these parameters, in addition to the effects of cooling itself on these organs. Abbreviations: CI, confidence interval; ECMO, extracorporeal membrane oxygenation; FFP, fresh frozen plasma; OR, odds ratio; PPHN, persistent pulmonary hypertension of the newborn; SHC, selective head cooling; WBC, whole body cooling.…”
Section: Discussionmentioning
confidence: 52%
“…We assessed the relative effects of WBC and SHC on most of the clinically important components of multiorgan system dysfunction commonly seen during the three earlier large randomized cooling trials, 6,7,14 and in one systematic review of five of the earlier cooling trials. 15 The severity of hypoxic-ischemic insult was similar between the WBC and SHC groups as clinical and laboratory evidence of an intrapartum hypoxic-ischemia was similar at the initiation of cooling.…”
Section: Effects Of Therapeutic Hypothermia S Sarkar Et Almentioning
confidence: 99%
“…38 Initial pilot studies in human newborns described reproducible approaches to both selective head and whole-body hypothermic therapy and confirmed the feasibility of such therapies. [39][40][41][42][43][44] Although these studies noted mild physiological changes in cardiovascular status and the potential for minor permutations in coagulation measurements, they showed that these changes were not clinically significant, that both methods of cooling were practical and that there were no major short-term consequences or complications to either method of cooling. On the basis of these pilot studies, larger clinical trials in newborns (described below) have been performed.…”
Section: Therapeutic Hypothermiamentioning
confidence: 98%
“…[4][5][6][7] Esta intervención terapéutica es más efectiva cuanto más temprana sea aplicada y dentro de una ventana terapéutica comprendida dentro de las seis horas de vida. Una vez alcanzada la temperatura objetivo de 33 o C-34 o C, esta hipotermia moderada debe ser mantenida durante 72 horas, tras lo cual se realiza un recalentamiento lento.…”
Section: Información Generalunclassified